Effect of High Dose Folic Acid Supplementation on the Prevention of Pre-Eclampsia in Pregnancy with Hypertension - Zhou, Chaoyou; Li, Qiongshan; Zhou, Yinjian; Xu, Zhuangzhuang; Jin, Yan (Indian Journal of Pharmaceutical Education and Research, 2025)
Background “Pre-eclampsia” is one of the most dangerous pregnancy complications, increasing the risk of both the mother and the baby dying prematurely. Because there have been conflicting findings on whether folic acid can reduce the incidence of pre-eclampsia, we conducted a randomized clinical trial of high-dose folic acid administration to pregnant women at a high risk of pre-eclampsia. Materials and Methods The study was a randomized clinical trial involving 1500 pregnant women. These women were randomly assigned into the Folic acid group (n=750) and Placebo group (n=750). From randomization (gestation period of 8 to 16 complete weeks) to birth, group 1 received 4mg of folic acid and group 2 received placebo per day. Participants were also analyzed for compliance over ≤50%, 50-<75% and ?75%. Four follow-ups were scheduled at 24-26, 34-36 gestational weeks, after birth and 42 days post-partum. The primary outcome measure was the incidence of pre-eclampsia. In contrast, secondary outcome measures included early pre-term birth, stillbirth, neonatal death, perinatal mortality, early-onset sepsis and admission to NICU for 24 hr or more. Results The present investigation showed that the incidence of pre-eclampsia was significantly lower in the folic acid group compared to placebo group (5.3% vs 10%) with a Risk Ratio (RR) of 0.53 95% Confidence Interval (CI): 0.53 to 0.79. Similarly, the incidence of secondary outcomes was also reduced in the folic acid group compared to the placebo group. Conclusion The results of the study lend support to the idea that pregnant women with “hypertension” should take high-dose folic acid supplements as a prophylactic measure against pre-eclampsia.
Keywords: Pre-eclampsia; Folic acid; Pregnant women; Primary outcome; Secondary outcome; Hypertension